Game design workshop : a playcentric approach to creating innovative games - Fullerton, Tracy (Boca Raton : CRC Press/Taylor & Francis, 2014)
"Since the publication of the second edition, many changes have occurred in the games industry, from an increase in multitouch screen platforms to a rise in smaller teams and development companies and more independent designers. This third edition expands discussions of new platforms and genres of play as well as processes, such as agile development (SCRUM). This edition emphasizes how to work with analytics to improve game play experience and the commercial viability of games. It also includes interviews with a number of independent designers"--
"An A K Peters book."
Includes bibliographical references and index.
Keywords: Computer games -- Programming; Computer games -- Design; Computer graphics